The Seattle Care Pathway for securing oral health in older patients - Pretty, Iain A.; Ellwood, Roger P.; Lo, Edward C.M.; MacEntee, Michael I.; Müller, Frauke; Rooney, Eric; Murray Thomson, William; Van der Putten, Gert-Jan; Ghezzi, Elisa M.; Walls, Angus; Wolff, Mark S. (Gerodontology, 2014)
There is a need for a structured, evidence based approach to care for older dental patients. The following article describes the development of the Seattle Care Pathway based upon a workshop held in 2013. An overview is provided on the key issues of older persons dental care including the demography shift, the concept of frailty, the need for effective prevention and treatment to be linked to levels of dependancy and the need for a varied and well educated work force. The pathway is presented in tabular form and further illustrated by the examples in the form of clinical scenarios. The pathway is an evidence based, pragmatic approach to care designed to be globally applicable but flexible enough to be adapted for local needs and circumstances. Research will be required to evaluate the pathways application to this important group of patients.